2013
DOI: 10.1183/09031936.00187812
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peroxisome proliferator-activated receptor-  ligands on in vitro and in vivo models of COPD

Abstract: Peroxisome proliferator-activated receptor (PPAR)-c is expressed in alveolar macrophages. The anti-inflammatory potential of the PPAR-c ligands rosiglitazone and pioglitazone were investigated using in vitro alveolar macrophage models and in vivo animal models relevant to chronic obstructive pulmonary disease (COPD).PPAR-c protein and gene expression in COPD alveolar macrophages was compared with control smokers and never-smokers. COPD macrophages were used to investigate the effects of PPAR-c ligands and cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 43 publications
5
68
0
Order By: Relevance
“…Other previous investigations have shown that PPAR␥ activation can attenuate inflammation either in animal models of COPD or following CSE exposure in vitro, but have not addressed the signaling pathways we investigated. Both the thiazolidinedione pioglitazone (29) and the endogenous PPAR␥ agonist 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) (30) have proven effective in the LPS-induced model of COPD, while both Rosi and pioglitazone were effective in a smoke-induced model (28). In vitro, Lee et al (31) attributed the ability of Rosi to inhibit CSE-induced TNF-␣ and mucin production in H292 cells to up-regulation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN), with consequent down-regulation of the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous investigations have shown that PPAR␥ activation can attenuate inflammation either in animal models of COPD or following CSE exposure in vitro, but have not addressed the signaling pathways we investigated. Both the thiazolidinedione pioglitazone (29) and the endogenous PPAR␥ agonist 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) (30) have proven effective in the LPS-induced model of COPD, while both Rosi and pioglitazone were effective in a smoke-induced model (28). In vitro, Lee et al (31) attributed the ability of Rosi to inhibit CSE-induced TNF-␣ and mucin production in H292 cells to up-regulation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN), with consequent down-regulation of the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown a strong correlation between PPARγ gene expression and protein activity suggesting that this method is acceptable [164]. Previous studies assessing airway PPARγ expression in association with disease states have also arrived at similar conclusions [114,115], meaning that this study is consistent with the reported literature of a down regulation of PPARγ in inflammatory airways diseases. Another limitation could be the baseline differences between the healthy control and the bronchiectasis group.…”
Section: Limitationssupporting
confidence: 82%
“…Inhibition of PPARγ has been shown to produce a pro-inflammatory phenotype by interfering with its inhibitory action on the target genes of NFκB [113]. PPARγ production has been shown to be down-regulated in inflammatory airways diseases, including COPD [114] and CF [115], suggesting its suppression is involved in the underlying pathology. In vitro studies have demonstrated that the presence of P. aeruginosa AHLs suppress expression of PPARγ [111,115].…”
Section: Interaction With Pparγmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxisome proliferator-activated receptor-γ (PPARγ) agonists are members of the nuclear receptor family that exert in pre-clinical studies anti-inflammatory effects potentially relevant to the treatment of airway diseases and to restoring corticosteroid sensitivity [141,142]. A proof of concept study using the oral PPARγ agonist rosiglitazone demonstrated bronchodilator effects in mild to moderate smokers with asthma who had non-eosinophilic inflammation [143].…”
Section: Pparγ Agonistsmentioning
confidence: 99%